ROS-Mediated NLRP3 Inflammasome Activity Is Essential for Burn-Induced Acute Lung Injury - Shichao Han; Weixia Cai; Xuekang Yang; Yanhui Jia; Zhao Zheng; Hongtao Wang; Jun Li; Yan Li; Jianxin Gao; Lei Fan; Dahai Hu (Mediators of Inflammation)
The NLRP3 inflammasome is necessary for initiating acute sterile inflammation. However, its role in the pathogenesis of burn-induced acute lung injury (ALI) is unknown. This study aimed to determine the role of the NLRP3 inflammasome and the signaling pathways involved in burn-induced ALI. We observed that the rat lungs exhibited enhanced inflammasome activity after burn, as evidenced by increased levels of NLRP3 expression and Caspase-1 activity and augmented inflammatory cytokines. Inhibition of NLRP3 inflammasome by BAY11-7082 attenuated burn-induced ALI, as demonstrated by the concomitant remission of histopathologic changes and the reduction of myeloperoxidase (MPO) activity, inflammatory cytokines in rat lung tissue, and protein concentrations in the bronchoalveolar lavage fluid (BALF). In the in vitro experiments, we used AMs (alveolar macrophages) challenged with burn serum to mimic the postburn microenvironment and noted that the serum significantly upregulated NLRP3 inflammasome signaling and reactive oxygen species (ROS) production. The use of ROS scavenger N-acetylcysteine (NAC) partially reversed NLRP3 inflammasome activity in cells exposed to burn serum. These results indicate that the NLRP3 inflammasome plays an essential role in burn-induced ALI and that burn-induced NLRP3 inflammasome activity is a partly ROS-dependent process. Targeting this axis may represent a promising therapeutic strategy for the treatment of burn-induced ALI.